2023
DOI: 10.1021/acsomega.2c07783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Carboxymethyl Cellulose on the Dynamic Wetting Characteristics of the Dust Suppression Droplet Impacting the Coal Surface

Fangwei Han,
Yue Zhao,
Mei Liu
et al.

Abstract: The dynamic wetting behavior of droplets impacting the coal surface directly affects the efficient application of waterbased dust suppression materials in coal-related industrial production. In this paper, ultrapure water, Tween-80, and sodium carboxymethyl cellulose are taken as the research objects. Using high-speed photography technology, the spreading, oscillation process, and splash morphology of many kinds of droplets during impacting the coal surface are captured. The effects of viscosity, surface tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Considering the use of sodium carboxymethylcellulose as a polymer matrix for BC dispersion, results in Figure 6d showed that sedimentation percentage settled around 30% after a week: (36 ± 2)%, (31 ± 2)% and (27 ± 2)% for 10.0, 15.0, and 20.0 g/L, respectively. Being an anionic polysaccharide, CMC show coagulation characteristic and tends to form micellar-like structure absorbing a considerable amount of water [65], thus being suitable as a support matrix for biochar. Moreover, CMC shows some advantages compared with other polymers, (i) it does not require heating for complete dissolution, (ii) it is soluble in water in a wide range of pHs, and (iii) led to a slightly basic S1 for complete pH values) with long-term stability.…”
Section: Sedimentation Testsmentioning
confidence: 99%
“…Considering the use of sodium carboxymethylcellulose as a polymer matrix for BC dispersion, results in Figure 6d showed that sedimentation percentage settled around 30% after a week: (36 ± 2)%, (31 ± 2)% and (27 ± 2)% for 10.0, 15.0, and 20.0 g/L, respectively. Being an anionic polysaccharide, CMC show coagulation characteristic and tends to form micellar-like structure absorbing a considerable amount of water [65], thus being suitable as a support matrix for biochar. Moreover, CMC shows some advantages compared with other polymers, (i) it does not require heating for complete dissolution, (ii) it is soluble in water in a wide range of pHs, and (iii) led to a slightly basic S1 for complete pH values) with long-term stability.…”
Section: Sedimentation Testsmentioning
confidence: 99%